PERCUTANEOUS RADIOLOGIC GASTROSTOMY: RESULTS AND COMPLICATIONS - Chishty, Ishtiaq A; Haider, Zishan; Khan, Dawar; Pasha, Sajida; Rafiq, Zafar; Akhter, Waseem (Journal of Ayub Medical College Abbottabad, 2006)
Background: Percutaneous endoscopic gastrostomy is usually difficult in patients with malignant involvement of oral cavity, pharynx and esophagus. Flouroscopic guided insertion of Gastrostomy catheter with Gastropexy have gained acceptance because it is easy and less time consuming as well as less invasive as compare to surgical procedure5. This study was done to evaluate the safety and efficacy of percutaneous placement of gastrostomy with gastropexy using imaging guidance in patients with oropharyngeal and esophageal cancers. Methods: Over five years, 105 patients were referred to our department for percutaneous radiologic gastrostomy. In five patients the procedure was not performed because of overlying viscera and high position of stomach. We performed 100 gastrostomies with gastropexy procedures using seldinger technique. Results: Success rate for percutaneous radiologic gastrostomy was 100%. No major complication had occurred. There were 11 minor complications occurred including 4 stomal infection, 3 catheter obstruction, one peritonism and three were extensive pneumoperitoneum. Stomal infection and catheter obstruction were not related to procedure. So, our true minor complications were only 4 (4%) which is comparable to literature. Conclusion: Percutaneous radiologic gastrostomy is an effective and safe procedure for enteric access of nutrition in patients with oral, pharyngeal and esophageal cancer where percutaneous endoscopic gastrostomy is difficult. Keywords: Interventional procedure, Complications, Gastrostomy